Coping strategies for activities of daily living in women whose hands affected by systemic sclerosis. Issue 11 (12th December 2013) - Cinar, Fatma I; Unver, Vesile; Cinar, Muhammet; Yilmaz, Sedat; Simsek, Ismail; Tosun, Nuran; Erdem, Hakan; Yilmaz, Fatma; Pay, Salih; Dinc, Ayhan
<x xml:space="preserve">Abstract</x> Aims and objectives To determine the challenges experienced by women with systemic sclerosis, whose hands affected, while performing activities of daily living and their coping strategies. Background Many of the patients with systemic sclerosis experience difficulties in performing daily activities. One of the most important reasons for that is the impaired hand function due to their diseases. Design A descriptive cross‐sectional design was conducted and questionnaire was used in this study. Methods The study was performed in a Rheumatology Department at a tertiary‐care hospital in Turkey between April 2010–December 2011. Nineteen patients with systemic sclerosis with hand involvement were enrolled in this study. The data were collected by using both a demographic data form and an Evaluation of Daily Activity Questionnaire. Results According to Evaluation of Daily Activity Questionnaire, the most scored dimension that patients can do with much difficulty was 'eating' and the dimension that patients unable to do was 'washing/clothes care'. In 'eating' dimension, the most difficult activities were 'opening glass jar', 'opening juice bottle' and 'opening bottle' that requiring the movement of rotation. Their coping strategies for these activities were as follows: try to open with a towel, try to remove the edge of the palm with a knife, use the hand palm and help from someone else (spouse, neighbour, etc.). In 'washing/clothes care' dimension, the most difficult activities were 'turning up hem of a skirt', 'washing up in bowl' and 'cutting out material'. For these activities, they use some coping strategies such as getting help from tailor, washing in the machine instead of hand washing. Conclusion This study demonstrates that impaired hand function affects the daily life activities of patients with systemic sclerosis, and patients have developed some coping strategies to overcome these difficulties. Relevance to clinical practice The coping strategies used by patients can be helpful for the other patients with systemic sclerosis.